PENJADWALAN PERAWATAN MESIN PRESSURE JET INCINERATOR DENGAN METODE RCM BERDASAR DOWNTIME ANALYSIS DAN FMEA - Budiharjo (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
During 2013 PT. CWI as a solid waste processing services company did not reach its waste processing capacity target due to 62 pressure jet incinerator engine component failures, resulting in high downtime, namely 880 hours or an average of 73.33 hours per month. This repeated failure is due to the equipment maintenance system which is still carried out correctively. This research aims to create a preventive maintenance schedule to improve the maintenance system which has been carried out using the Reliability Centered Maintenance (RCM) method based on downtime analysis using the Failure Mode and Effect Analysis (FMEA) method approach. Based on downtime analysis, it is known that the average Operational Availability value for pressure jet incinerator machines is 87.21%, still below the word class standard of 90%. From the FMEA analysis, it was found that the component that was most critical and most at risk as a cause of failure was the Refractory Body with an RPN of 240, far above the RPN threshold of 88.6. Other components that are dominant as causes of failure are the Burner, Electric Motor, and Wet Scrubber. With the RCM method, preventive maintenance scheduling can be proposed in the form of a preventive maintenance job schedule in order to improve the corrective maintenance system into a preventive maintenance system.